DETEKSI CEMARAN BAKTERI Escherichia coli PADA JAMU KUNYIT TEMULAWAK YANG DIJUAL DI KECAMATAN SINGAPARNA KABUPATEN TASIKMALAYA DENGAN METODE MPN (Most Probable Number): Deteksi Cemaran Bakteri Escherichia Coli pada Jamu Kunyit Temulawak yang Dijual Di Kecamatan Singaparna Kabupaten Tasikmalaya dengan Metode MPN (Most Probable Number) - Aqil, Azril Haeruman; Fadilah, Nitya Nurul; Susanti, Susanti (Berkala Ilmiah Kimia Farmasi, 2025)
One type of traditional herbal medicine that is widely consumed by the public is turmeric-javanese ginger erbal medicine, which is considered to have many health benefits, such as increasing appetite and curing digestive problems. However, unhygienic processing can cause microbial contamination, one of which is Escherichia coli bacteria which has the potential to cause diarrhea. Using the MPN (Most Probable Number) method, this study aims to evaluate the presence and level of Escherichia coli contamination in turmeric-javanese ginger herbal medicine sold in the Singaparna District area. There are 10 herbal medicine sellers who use plastic bottle packaging to collect samples. The prediction test with LB media, the confirmation test with BGLB media, and the complementary test with EMBA media were carried out simultaneously and the Gram staining test of bacteria was carried out. The results showed that most of the samples were contaminated with Escherichia coli with MPN values ​​ranging from 3.6 to 150 MPN/mL, exceeding the threshold of SNI 7388 Year 2009 (<3 MPN/mL). Gram staining confirmed that the bacteria were Gram-negative in the form of bacilli. These findings indicate the need for improved hygiene and sanitation in the process of making herbal medicine to ensure consumer safety.   Keywords: Contamination, Escherichia coli, Jamu Kunyit Temulawak, MPN